A new species of Pygoluciola Wittmer with unusual abdominal configuration, from lowland dipterocarp forest in Peninsular Malaysia (Coleoptera: Lampyridae: Luciolinae) - Nada, B.; Ballantyne, L. A. (Zootaxa, 2018)
A new species of firefly (Coleoptera: Lampyridae) Pygoluciola dunguna Nada sp. nov. is described from males and reliably associated females, collected mainly from lowland dipterocarp forests of Peninsular Malaysia at elevations below 300 m a.s.l. This species is found to be terrestrial, flying at low heights between 10−15 m above ground in between the herbaceous plants. Males are intermediate between the two types of Pygoluciola Wittmer known until now. A list of species, and a key to males and known females of Pygoluciola is given. The female bursa has paired elongate hook like bursa plates.